Methodological recommendations for assessing the quality of science and technology project management process at the scientific research stage on the basis of higher education institution - K. A. Brazhnikova; D. E. Ilts (Омский научный вестник)
The research presents the analysis of the existing tools for ensuring the quality of the process of the scientific and technical projects management at all stages of the life cycle, implemented on the basis of higher education institution. The authors studied the life cycle of the project from the scientific idea to the final production or license sale and the stage of research and development, for which the proposed recommendations are considered. Moreover, the conceptual bases of the quality of scientific and technical project management process for the purpose of successful commercialization by the example of oil product container development are formed. Methodical recommendations on risk management of scientific and technical project are demonstrated. The presented materials can be used in the development of methodological recommendations for assessing the quality of the management of scientific and technical project to obtain the appropriate economic effect.